Analisis Disparitas Pendapatan Antar Kabupaten/Kota di Provinsi Aceh - Marzalina Marzalina (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
The study is intended to investigate whether district’s income disparities exist in Aceh. Secondary data published by provincial statistic board and provincial planning and development board were used from 2008 to 2012. The results of the study revealed that income disparty among districts in Aceh existed. There were some developed districts among others Aceh Tengah, Aceh Barat, Aceh Besar, Nagan Raya, Banda Aceh and Sabang.Meanwhile, Aceh Timur,Aceh Utara and Lhokseumawe showed stagnant development. But, Simeulue, Aceh Singkil, Aceh Selatan, Aceh Tenggara, Pidie, Aceh Barat Daya, Gayo Lues, Aceh Tamiang, Aceh Jaya, Bener Meuriah, Pidie Jaya, Langsa and Subussalam were categorized as less developed districts. Based on the results of the study, both provincial and districts governments have to work together to minimize inhibiting factors that may affect income equality.